Math, asked by kiransingh4256, 1 year ago

tan theta minus cot theta equal to sin square theta minus one upon sin theta cos theta​

Answers

Answered by Ayushi2611
0

Step-by-step explanation:

is that your question?

Attachments:
Answered by harendrachoubay
1

\tan \theta-\cot \theta=\dfrac{2\sin^2 \theta-1}{\sin \theta\cos \theta}, proved.

Step-by-step explanation:

To prove that, \tan \theta-\cot \theta=\dfrac{2\sin^2 \theta-1}{\sin \theta\cos \theta}.

L.H.S. =\tan \theta-\cot \theta

\tan \theta = \dfrac{\sin \theta}{\cos \theta} and

\cot \theta = \dfrac{\cos \theta}{\sin \theta}

=  \dfrac{\sin \theta}{\cos \theta}-\dfrac{\cos \theta}{\sin \theta}

=  \dfrac{\sin^2 \theta-\cos^2 \theta}{\sin \theta\cos \theta}

=  \dfrac{\sin^2 \theta-(1-\sin^2 \theta)}{\sin \theta\cos \theta}

=  \dfrac{\sin^2 \theta-1+\sin^2 \theta}{\sin \theta\cos \theta}

= \dfrac{2\sin^2 \theta-1}{\sin \theta\cos \theta}

= R.H.S. , proved.

Thus, \tan \theta-\cot \theta=\dfrac{2\sin^2 \theta-1}{\sin \theta\cos \theta}, proved.

Similar questions